2020
DOI: 10.1007/s11356-020-08853-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac toxicity of acrolein exposure in embryonic zebrafish (Danio rerio)

Abstract: Acrolein is a widely distributed pollutant produced from various sources such as industrial waste, organic combustion, and power plant emissions. It is also intentionally released into irrigation canals to control invasive aquatic plants. Zebrafish (Danio rerio) has a good reputation for being an attractive model organism for developmental and toxicological research. In this study, zebrafish embryos were exposed to acrolein to investigate the cardiotoxic effects. The 96-h LC 50 (median lethal concentration) va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Several investigators reported the presence of hazardous carbonyl compounds such as formaldehyde, acetaldehyde, glyoxal, and acrolein in EC aerosol (Bekki et al 2014 ; Etter, Zäther, and Svensson 2013 ; Ogunwale et al 2017 ; Schober et al 2014 ) and tobacco-specific N-nitrosamines (TSNA) in e-liquids and their aerosols (Farsalinos et al 2015 ). Acetaldehyde and formaldehyde are recognized carcinogens (Feron et al 1991 ; Roe and Wood 1992 ), and acrolein is a cardiovascular toxicant (Arman and İşisağ Üçüncü 2020 ; DeJarnett et al 2014 ). Tobacco-specific N-nitrosamines are carcinogenic compounds formed from the curing and processing of tobacco leaves through nitrosation of nicotine and related tobacco alkaloids (Bush et al 2001 ; Wang et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators reported the presence of hazardous carbonyl compounds such as formaldehyde, acetaldehyde, glyoxal, and acrolein in EC aerosol (Bekki et al 2014 ; Etter, Zäther, and Svensson 2013 ; Ogunwale et al 2017 ; Schober et al 2014 ) and tobacco-specific N-nitrosamines (TSNA) in e-liquids and their aerosols (Farsalinos et al 2015 ). Acetaldehyde and formaldehyde are recognized carcinogens (Feron et al 1991 ; Roe and Wood 1992 ), and acrolein is a cardiovascular toxicant (Arman and İşisağ Üçüncü 2020 ; DeJarnett et al 2014 ). Tobacco-specific N-nitrosamines are carcinogenic compounds formed from the curing and processing of tobacco leaves through nitrosation of nicotine and related tobacco alkaloids (Bush et al 2001 ; Wang et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This advanced in vivo imaging method has been widely used to assess changes in embryonic hemodynamics under normal and stressed conditions during the early developmental stages ( Midgett and Rugonyi, 2014 ; Yalcin et al, 2017 ; Benslimane et al, 2020 ; Salman and Yalcin, 2020 ). Another technique widely considered to access structural damages in different organ tissues is histology ( Naïja et al, 2017 , 2018 ; Arman and Üçüncü, 2020 ). In chick embryos, Sedmera et al (2002) and Tobita and Keller (2000) highlighted the importance of the histopathological technique in detecting abnormalities of heart macroelements.…”
Section: Introductionmentioning
confidence: 99%